An Analysis of the Eurasian Tectonic Plate Motion Parameters Based on GNSS Stations Positions in ITRF2014 - Marcin Jagoda; Miłosława Rutkowska (Sensors, 2020)
The article is the fourth part of our research program concerning an analysis of tectonic plates’ motion parameters that is based on an observation campaign of an array of satellite techniques: SLR, DORIS, VLBI, and now GNSS. In this paper, based on the International Terrestrial Reference Frame 2014 (ITRF2014) for observations and using the GNSS technique, the Eurasian tectonic plate motion was analyzed and the plate motion parameters Φ, Λ (the position of the rotation pole), and ω (the angular rotation speed) were adjusted. Approximately 1000 station positions and velocities globally were obtained from the GNSS campaign over a 21-year time interval and used in ITRF2014. Due to the large number of data generated using this technique, the analyses were conducted separately for each tectonic plate. These baseline data were divided into a number of parts related to the Eurasian plate, and are shown in this paper. The tectonic plate model was analyzed on the basis of approximately 130 GNSS station positions. A large number of estimated station positions allowed a detailed study to be undertaken. Stations that agree with the plate motion were selected and plate parameters were estimated with high accuracy. In addition, stations which did not agree with the tectonic plate motion were identified and removed. In the current paper, the influence of the number and location of stations on the computed values and accuracy of the tectonic plate motion parameters is discussed. Four calculation scenarios are examined. Each scenario contains 30 stations for the common solution of the European and Asiatic part of the Eurasian plate. The maximum difference between the four calculation scenarios is 0.31° for the Φ parameter and 0.24° for the Λ parameter, indicating that it is at the level of the value of the formal error. The ω parameter has the same value for all the scenarios. The final stage of the analysis is the estimation of parameters Φ, Λ, and ω based on all of the 120 stations used in the four calculation scenarios (i.e., scenario 1 + scenario 2 + scenario 3 + scenario 4). The following results are obtained: Φ = 54.81° ± 0.37°, Λ = 261.04° ± 0.48°, and ω = 0.2585°/Ma ± 0.0025°/Ma. The results of the analysis are compared with the APKIM2005 model and another solution based on the GNSS technique, and a good agreement is found.